Association between genetically proxied glucosamine and risk of cancer and non-neoplastic disease: A Mendelian randomization study - Wu, Yingtong; Che, Yinggang; Zhang, Yong; Xiong, Yanlu; Shu, Chen; Jiang, Jun; Li, Gaozhi; Guo, Lin; Qiao, Tianyun; Li, Shuwen; Li, Ou; Chang, Ning; et al. (Frontiers in Genetics, 2024)
Introduction Observational investigations have examined the impact of glucosamine use on the risk of cancer and non-neoplastic diseases. However, the findings from these studies face limitations arising from confounding variables, reverse causation, and conflicting reports. Consequently, the establishment of a causal relationship between habitual glucosamine consumption and the risk of cancer and non-neoplastic diseases necessitates further investigation. Methods For Mendelian randomization (MR) investigation, we opted to employ single-nucleotide polymorphisms (SNPs) as instruments that exhibit robust associations with habitual glucosamine consumption. We obtained the corresponding effect estimates of these SNPs on the risk of cancer and non-neoplastic diseases by extracting summary data for genetic instruments linked to 49 varied cancer types amounting to 378,284 cases and 533,969 controls, as well as 20 non-neoplastic diseases encompassing 292,270 cases and 842,829 controls. Apart from the primary analysis utilizing inverse-variance weighted MR, we conducted two supplementary approaches to account for potential pleiotropy (MR-Egger and weighted median) and assessed their respective MR estimates. Furthermore, the results of the leave-one-out analysis revealed that there were no outlying instruments. Results Our results suggest divergence from accepted biological understanding, suggesting that genetically predicted glucosamine utilization may be linked to an increased vulnerability to specific illnesses, as evidenced by increased odds ratios and confidence intervals (95% CI) for diseases, such as malignant neoplasm of the eye and adnexa (2.47 [1.34–4.55]), benign neoplasm of the liver/bile ducts (2.12 [1.32–3.43]), benign neoplasm of the larynx (2.01 [1.36–2.96]), melanoma (1.74 [1.17–2.59]), follicular lymphoma (1.50 [1.06–2.11]), autoimmune thyroiditis (2.47 [1.49–4.08]), and autoimmune hyperthyroidism (1.93 [1.17–3.18]). In contrast to prior observational research, our genetic investigations demonstrate a positive correlation between habitual glucosamine consumption and an elevated risk of sigmoid colon cancer, lung adenocarcinoma, and benign neoplasm of the thyroid gland. Conclusion Casting doubt on the purported purely beneficial association between glucosamine ingestion and prevention of neoplastic and non-neoplastic diseases, habitual glucosamine ingestion exhibits dichotomous effects on disease outcomes. Endorsing the habitual consumption of glucosamine as a preventative measure against neoplastic and non-neoplastic diseases cannot be supported.